Feasibility study on hydrogen power plant using hydrogen production by photocatalysis - Calunsag, Rene Jr; Peralta, Mychal Chase; Revilloza, Therese Marie; Rosete, Paola Marie
Hydrogen power plants will provide renewable energy without producing any wastes, using only water, sunlight, and a unique photocatalyst.In a world where carbon emissions are highly regulated, pollution of the rivers and skies are major concerns, and the primary sources of energy - oil, coal, and natural gas - are running out, the call for clean, sustainable, renewable energy sources may be one of the most urgent challenges today. Hydrogen power plants may be a solution. It is found that by supplying 1% of the projected demand-supply gap in Mindanao, a revenue of more than PhP 100 M may be earned per year (a power plant capacity of 1.2 MW). This is 0.12% of the total power supply in the area. In terms of carbon emissions alone, a non-polluting power plant of this capacity is able to save a worth of at least PhP 8 B according to the Kyoto Protocol. Furthermore, there is no mining activity and no water-polluting activities in any stage of power production with this novel technology. Issues identified due to the infancy stage of this technology include inaccuracy of sacrificial agent consumption and extremely conservative lifetime estimate of the photocatalyst. Both problems will be solved by further studies. As the industry must eventually wean off non-renewables, hydrogen power may be a lead candidate for the power source of the future.